Apie metodologinį filosofijos vaidmenį bibliografinių objektų pažinime - Janonis, Osvaldas (Knygotyra, 2026)
Practical and scientific needs of bibliography require a deeper investigation of methodological problems. The article deals with the methodological relation and proportion of bibliography with the philosophical methodological level. It comprises the methodological function of cognizant forms and means, i. e. methods, principles, categories and laws, in the cognition of bibliographical objects and phenomena. Modern stage of bibliography development requires a more extensive and conscientious use of all the possibilities provided by philosophical and methodological level, as well as the development of the philosophical culture among the bibliography scientific workers.